Revisiting the Trade Impact of the African Growth and Opportunity Act : A Synthetic Control Approach - Kassa, Woubet; Coulibaly, Souleymane (World Bank, Washington, DC, 2019)
This study examines the impact of the African Growth and Opportunity Act using the synthetic control method, a quasi-experimental approach. The novelty in the approach is that it addresses problems of estimation that are prevalent in nonexperimental methods used to analyze the impact of preferential trade agreements. The findings show that most of the eligible countries registered gains in exports due to the African Growth and Opportunity Act. However, the results are varied, and the gains were largely unsteady. Much of the gains are due to exports of petroleum and other minerals, while there are few countries that were able to expand into manufacturing and other industrial goods. The positive trade impacts were largely associated with improvements in information and communications technology infrastructure, integrity in the institutions of legal and property rights, ease of labor market regulations, and sound macroeconomic environment, including stable exchange rates and low inflation. Undue exposure to a single market, like the United States, or few commodities may have also restricted the gains from trade.